The Russian prepositional TIPA and VRODE in online student discourse: evidence of attraction? - Kolyaseva Alena (Linguistics)
This article scrutinizes the use of two competing Russian prepositions, tipa and vrode ‘like, such as’, in online student discourse. Both are associated with the crosslinguistically attested grammaticalization of taxonomic nouns, with tipa having derived from the noun tip ‘type’ and vrode from the noun rod ‘kind’. A prior study contemporary to the fairly recent grammaticalization of tipa forecasted a substitution scenario for the two competing forms. Forty years later, the present article shows that in the current discourse of younger speakers (i) there is indeed a selectional bias in favor of the prepositional tipa (which does not extend to the items’ particle uses) and (ii) the two prepositions demonstrate a high degree of attraction. However, this article also provides quantitative evidence that suggests the presence of a counterforce – subjectification. The selection is modeled on the basis of the items’ functions, realizations of the right- and left-side slots, the speaker’s gender, their evaluative attitude to the referent of the construction, and the perceived casualness of the discourse situation proxied by neutral or markedly informal expression styles.